Allergenic and novel food proteins: State of the art and challenges in the allergenicity assessment. (February 2019) - Pali-Schöll, Isabella; Verhoeckx, Kitty; Mafra, Isabel; Bavaro, Simona L.; Clare Mills, E.N.; Monaci, Linda
Abstract: Background: There is an increasing demand for animal-derived products in the developing countries. This poses major concerns for the sustainable production of safe and nutritious food. Consequently, to address these needs alternative sustainable sources of valuable dietary proteins are sought for. Scope and approach: In this review, we discuss alternative protein sources for human food consumption such as novel foods derived from other animal sources like insects. Before these novel foods can enter the market place, their safety for consumers should be demonstrated. We herein provide an overview of the legislative framework currently in place across Europe, the key elements required for allergenicity assessment of novel foods, the tools at disposal for allergenicity prediction and the most advanced technologies available for food allergen detection and characterization. Key finding and conclusions: Effective characterization of potential protein-based allergenic hazards in novel food ingredients is essential to support effective risk assessment. Development of a cost-effective, validated tool box to allow improved hazard characterization for allergenicity risk assessment is needed. Although novel methodologies, such as mass spectrometry, have great potential for allergen characterization and allergen detection in different food contributing to reduce the risk for allergic consumers, some work is still required for method validation and the creation of protein sequence databases for proteomic analysis. Highlights: Characterization of potential protein-based allergenic hazards in novel food is essential for effective risk assessment. A cost-effective, validated tool box to improve hazard characterization for allergenicity risk assessment is needed. Efforts at EU level aim to improve the risk assessment, and develop and harmonize methods for allergenicity prediction.